Agricultural Adaptations and Depletion of the Ogallala Aquifer - Cao, Yunning. (Tufts University. Tisch Library., 2023)
Thesis (M.S.)--Tufts University, 2023.; Submitted to the Dept. of Economics.; Advisor: Ujjayant Chakravorty.; Committee: Jeffrey Zabel.; Keywords: Economics, and Agriculture economics.